The Influence Of Audit Fee, Audit Rotation, Audit Tenure, Company Size, Auditor Specialization And Auditor Reputation On Audit Quality In Manufacturing Companies Listed On The Indonesian Stock Exchange In 2020-2022 - Tanjung, Agustrial; Nasution, Nina Andriyani (Proceeding of The International Conference on Business and Economics, 2024)
The aim of this research is to determine the influence of Audit Fees, Audit Rotation, Audit Tenure, Company Size, Auditor Specialization and Auditor Reputation on Audit Quality in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The method used in this research is quantitative associative method, using secondary data. Based on the research results, it shows that Audit Fees, Audit Tenure and Auditor Specialization partially have no effect on Audit Quality. This shows that audit fees are low and competitive for auditors without reducing auditor quality standards. Audit quality is maintained even though there are changes in the Audit Tenure period. Auditor specialization is reduced, but there is increased training, application of audit standards and use of technology in maintaining effective Audit Quality. Company size partially has a positive and significant effect on Audit Quality. This shows that the auditor has sufficient expertise to handle the high complexity of a large company size, thus providing support for increasing audit quality. Audit Rotation and Auditor Reputation partially have a negative and significant effect on Audit Quality. This shows that a decrease in the frequency of Auditor Rotation can result in a decrease in their objectivity and independence, but auditors have a high perspective and long-term relationship to improve Audit Quality. A decline in auditor reputation can reduce public trust and auditor credibility, but implementing audit standards, strengthening policies and procedures and effective supervision can play a transparent role in maintaining integrity and professionalism by assessing and improving high audit quality standards. Audit Fees, Audit Rotation, Audit Tenure, Company Size, Auditor Specialization and Auditor Reputation simultaneously have a positive and significant effect on Audit Quality. This shows that Audit Fees can ensure auditors work well, Audit Rotation can reduce the risk of fraud, Optimal Audit Tenure does not lose objectivity, Company Size provides resources for comprehensive audits, Auditor Specialization adds value with special skills, Auditor Reputation adds trust and contribute to improving Audit Quality in Manufacturing Companies listed on the Indonesia Stock Exchange in 2020–2022.